Case report: Villaret's syndrome caused by middle ear adenocarcinoma in a cat - Kang, Dong-Jae; Park, Won-Keun; Kim, So-Yeon; Shin, Dong-Hoon; Park, Hee-Myung; Kang, Min-Hee (Frontiers in Veterinary Science, 2023)
A 7-year-old castrated male American Shorthair cat presented with left-side Horner's syndrome and voice change. The overall clinical presentation included dysphagia, intermittent coughing, unilateral miosis, and third eyelid protrusion of the left eye. A topical 1% phenylephrine was applied, and miosis and protrusion of the third eyelid disappeared within 20 min which suggested a post-ganglionic lesion. Laryngoscopy showed left-sided laryngeal paralysis. Computed tomography (CT) identified a mass lesion invading outside of the left tympanic bulla with osteolysis. Endoscopically assisted ventral bulla osteotomy was performed for tumor resection and definitive diagnosis. Middle ear adenocarcinoma was diagnosed based on histopathology. It appears that these neurological signs occurred due to adenocarcinoma in the tympanic bulla, penetrating the jugular foramen and the hypoglossal canal and damaging the cranial nerve IX (glossopharyngeal nerve), X (vagus nerve), XI (accessory nerve), and XII (hypoglossal nerve) and the sympathetic nerve. To the best of our knowledge, this is the first case report of Villaret's syndrome associated with middle ear adenocarcinoma affecting the nerves passing through the jugular foramen and hypoglossal canal in cats.